2016
DOI: 10.2741/s445
|View full text |Cite
|
Sign up to set email alerts
|

Elevated XPO6 expression as a potential prognostic biomarker for prostate cancer recurrence

Abstract: Recurrence of localized prostate cancer following treatment can lead to lethal metastatic castration-resistant prostate cancer. Although numerous studies aimed at developing biomarkers for predicting recurrence of localized prostate cancer are promising, they have not yet led to useful applications. Dysregulation of exportins (XPOs, nucleocytoplasmic transporters) associated with subcellular mislocalization of proteins has been reported for various human cancers. However, most of the XPOs have not been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…XPO6 was overexpressed and associated with metastatic potential and a poor prognosis in prostate cancer tissue [54]. Consistent with these findings, our analysis revealed higher XPO6 mRNA expression in HCC cancerous tissues compared with paracancerous liver tissues, and it was significantly related to HCC clinical stage and pathological grade.…”
Section: Discussionsupporting
confidence: 86%
“…XPO6 was overexpressed and associated with metastatic potential and a poor prognosis in prostate cancer tissue [54]. Consistent with these findings, our analysis revealed higher XPO6 mRNA expression in HCC cancerous tissues compared with paracancerous liver tissues, and it was significantly related to HCC clinical stage and pathological grade.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, TSR2 variation is associated with Diamond-Blackfan anemia (DBA) (Clinton and Gazda, 2009). As a nucleocytoplasmic transporter, XPO6 expression is closely related to poor prognosis of patients and is a potential prognostic biomarker for prostate cancer (Hao et al, 2016). ISG20 is involved in small nucleolar RNA maturation and ribosomal biogenesis, and controls RNA stability (Espert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This proposed mechanism along with statistical analysis of clinical datasets, led to the proposal that XPO6 expression correlates with poor survival in breast cancer patients. On the other hand, gene expression analysis of samples from prostate cancer patients showed that elevated levels of XPO6 can be used a prognostic marker of reoccurrence [61,62].…”
Section: Kap-mediated Nuclear Export and Cancermentioning
confidence: 99%